2022
DOI: 10.7759/cureus.21993
|View full text |Cite
|
Sign up to set email alerts
|

Ewing's Sarcoma (Primitive Neuroectodermal Tumor) of Seminal Vesicles: A Case Report

Abstract: Malignant tumors of the seminal vesicles are rare; they may be of epithelial or mesenchymal origin. Carcinomas are the most common and pelvic sarcoma may be confused with a primary tumor of the seminal vesicles. Little is known of the prognosis and best sequence of treatment in such sarcoma. We report a rare case of extra-skeletal Ewing sarcoma/primitive neuroectodermal tumor of the seminal vesicles in a 54-yearold man who presented with chronic lower abdominal pain, urinary retention, and severe constipation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 16 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…In this study, the prevalence of cardiotoxicity was 12.5%. The result was similar to our previous report of 12% cardiotoxicity occurrence among cancer patients during anticancer treatment in Najran City [ 4 ]. Prior studies have shown variable prevalences of cardiotoxicity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the prevalence of cardiotoxicity was 12.5%. The result was similar to our previous report of 12% cardiotoxicity occurrence among cancer patients during anticancer treatment in Najran City [ 4 ]. Prior studies have shown variable prevalences of cardiotoxicity.…”
Section: Discussionsupporting
confidence: 92%
“…The anticancer therapy agent was grouped into monoclonal agents, alkylating agents, anthracyclines agents, and taxans. The cardiac protection agents were grouped into beta-blockers, angiotensin-converting enzyme (ACE) inhibitors, statins, and antiplatelets [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations